2012
DOI: 10.1007/s00404-012-2330-6
|View full text |Cite
|
Sign up to set email alerts
|

Fetal growth restriction: current knowledge to the general Obs/Gyn

Abstract: Early diagnosis of FGR is very important, because it permits the etiological identification and adequate monitoring of fetal vitality, minimizing the risks related to prematurity and intrauterine hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
91
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 62 publications
1
91
0
4
Order By: Relevance
“…The most frequently studied long‐term repercussions of IUGR are those involving metabolic programming, which lead to the so‐called metabolic syndrome that is associated with a high risk of developing hypertension, diabetes, and cardiovascular disease. Nonetheless, longitudinal studies have also revealed a high incidence of learning, school and behavioral problems in IUGR babies compared with babies born at the same gestational age but with an adequate BW (Leitner et al., 2007; Nardozza et al., 2012). It is important to note that the diagnosis of true IUGR remains a challenge in clinical practice since children <10th percentile in size are not always pathological, and some children with appropriate weight for their gestational age might not have achieved their target growth (Campbell et al., 2012; Zhang et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently studied long‐term repercussions of IUGR are those involving metabolic programming, which lead to the so‐called metabolic syndrome that is associated with a high risk of developing hypertension, diabetes, and cardiovascular disease. Nonetheless, longitudinal studies have also revealed a high incidence of learning, school and behavioral problems in IUGR babies compared with babies born at the same gestational age but with an adequate BW (Leitner et al., 2007; Nardozza et al., 2012). It is important to note that the diagnosis of true IUGR remains a challenge in clinical practice since children <10th percentile in size are not always pathological, and some children with appropriate weight for their gestational age might not have achieved their target growth (Campbell et al., 2012; Zhang et al., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the growth potential in infants with CCHD is further complicated by the fact that cardiac lesion–specific differences in BW have been described 39. Additionally, with the lack of head circumference data, we were unable to distinguish between symmetric and asymmetric growth restriction 38. Future studies should focus on these unanswered questions and assess lesion‐specific outcomes to better understand the nuanced relationship between BW and GA in neonates with CCHD.…”
Section: Discussionmentioning
confidence: 98%
“…First, the data set used does not contain data on longitudinal intrauterine growth or information on head circumference, thus we were unable to assess fetal growth restriction per se because this term implies an in utero insult that led to a fetus not meeting its growth potential 38. Assessing the growth potential in infants with CCHD is further complicated by the fact that cardiac lesion–specific differences in BW have been described 39.…”
Section: Discussionmentioning
confidence: 99%
“…1 Fetuses with FGR have an increased risk for perinatal morbidity and mortality, impaired neurological and cognitive development during childhood and adolescence, and cardiovascular and endocrine disorders in adulthood. 2 Fetal growth restriction is characterized by cases wherein the fetus does not achieve full intrauterine growth and development because of impaired placental function. 1 However, in clinical practice, FGR is difficult to define, and there is currently no gold standard for its diagnosis.…”
mentioning
confidence: 99%
“…In the final stage, some possible algorithms were presented to experts, and the algorithm with the highest number of votes was considered the final algorithm for defining FGR. 2 The consensus concluded that the cutoff value between early and late FGR would be gestational age (GA) of 32 weeks, and the following parameters were used to define FGR in the absence of fetal malformations: early FGR (< 32 weeks): (i) fetal abdominal circumference below the third percentile for GA OR estimated fetal weight below the third percentile for GA OR zero diastole of the umbilical artery on Doppler (isolated criteria) and (ii) estimated fetal weight or waist circumference below the tenth percentile for GA AND the pulsatility index of the uterine and umbilical arteries above the 95th percentile for GA (combined parameters) and late FGR ( 32 weeks): (i) fetal abdominal circumference below the third percentile for GA OR estimated fetal weight below the third percentile for GA and (ii) the combination of at least two of the following parameters: (a) estimated fetal weight or fetal abdominal circumference below the tenth percentile for GA, (b) the reduction of more than two quartiles in the growth curve, and (c) the cerebroplacental association below the fifth percentile for GA or the pulsatility index of the umbilical artery above the 95th percentile for GA.…”
mentioning
confidence: 99%